MEASUREMENT OPTIMALIZATION OF ZAKAT DISTRIBUTION AT LEMBAGA AMIL ZAKAT USING VARIABLE MEASUREMENT OF ECONOMY - Haque, Marissa; Nasri, Rizfaldi; Nuraini, Nuraini; Yusuf, M (Bank Indonesia, 2016)
The aim of this research conducted is to optimalize the zakat distribution using economy variabel measurement. Design/Metodology. The Quantitative Research Method is used to analyze financial data, with Optimalize Model as Z variable design, Measurement of Economy as Y variable and Objective Output as X variable, using AMOS program and SEM as tool analysis to confirm that the model can be used as a measurement tool. Research result. Using some indicators to analyze every variable, obtaining output and objective result, influence optimalization of measurement of economy. Conclusion. The measurement of optimalization of zakat distribution using measurement of economy variable, with independent variable/output exogenous and objective, can be used as a model to measure Lembaga Amil Zakat performance. Furthermore, this research need to have some indicators’ development especially in the area of objective variable.